1989
DOI: 10.1093/bja/62.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Standard Intubating Position Using “Angle Finder”

Abstract: Study of patients who exhibit only limited morphological abnormality yet present difficulty with direct laryngoscopy is facilitated by a standard intubating position. The "Angle Finder" instrument allows implementation of a simple reproducible geometric standard which is applied easily in formal research work and in clinical practice and teaching. The proposed standard relates to the curved (Macintosh) laryngoscope blade and a supine patient. The lower neck flexion is 35 degrees and extension of the plane of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 7 publications
2
60
1
1
Order By: Relevance
“…~3,t4 As well, guidelines for the recognition and management of the difficult airway have recently been developed, t5 For the preoperative identification of patients with potentially difficult airways, several classifications have been proposed. [16][17][18][19][20][21][22] However, the various problems encountered when securing the airway and the morbidity during, or following, tracheal intubation have been poorly and incompletely defined in some studies. No reports have described the various methods of tracheal intubation used in large populations in the actual clinical setting, nor the outcome of different techniques and their associated difficulties.…”
Section: Cette Otude Porte Sur La Description Des M#thodes Des Factementioning
confidence: 99%
“…~3,t4 As well, guidelines for the recognition and management of the difficult airway have recently been developed, t5 For the preoperative identification of patients with potentially difficult airways, several classifications have been proposed. [16][17][18][19][20][21][22] However, the various problems encountered when securing the airway and the morbidity during, or following, tracheal intubation have been poorly and incompletely defined in some studies. No reports have described the various methods of tracheal intubation used in large populations in the actual clinical setting, nor the outcome of different techniques and their associated difficulties.…”
Section: Cette Otude Porte Sur La Description Des M#thodes Des Factementioning
confidence: 99%
“…[1][2][3][4] However, Adnet et al 5 recently demonstrated that the sniffing position does not achieve alignment of the axes of the mouth, pharynx and larynx in awake patients. They subsequently demonstrated that the sniffing position provides no advantage for improving the laryngoscopic view compared to simple head extension.…”
mentioning
confidence: 99%
“…12 For this reason, a standard intubating position has been proposed for use in intubation studies. 13 Despite this, the evident limitations of standardizing clinical studies convinced us that a successful evaluation of laryngoscope blades must initially derive from a theoretical basis. This paper outlines theoretical criteria for blade analysis and comparison based on previous investigative xray laryngoscopy studies.…”
mentioning
confidence: 99%